2013
DOI: 10.1074/jbc.m113.463455
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor α L543A,L544A Mutation Changes Antagonists to Agonists, Correlating with the Ligand Binding Domain Dimerization Associated with DNA Binding Activity

Abstract: Background: Helix 12 mutations of ER␣ reverse antagonists to agonists. Results: Antagonist-induced homodimerization of mutant ER␣ LBD coincides with DNA binding activity and antagonist reversal activity. Conclusions: Antagonist-dependent LBD homodimerization is an important step for antagonist reversal activity. Significance: This mechanism may be associated with the partial agonist activity of selective estrogen receptor modulators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
49
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 29 publications
4
49
1
Order By: Relevance
“…It was recently demonstrated in vitro that the ICI-dependent estrogen response element (ERE)-mediated transcriptional activity of the AF-2-mutated ERα is associated with the LBD dimerization activity (28). Furthermore, prevention of dimerization impaired the ICI-dependent activation and ERE binding of the AF-2-mutated ERα.…”
Section: Ici Acts As An Erα Agonist On Trabecular Bone Mass and Uterumentioning
confidence: 99%
See 3 more Smart Citations
“…It was recently demonstrated in vitro that the ICI-dependent estrogen response element (ERE)-mediated transcriptional activity of the AF-2-mutated ERα is associated with the LBD dimerization activity (28). Furthermore, prevention of dimerization impaired the ICI-dependent activation and ERE binding of the AF-2-mutated ERα.…”
Section: Ici Acts As An Erα Agonist On Trabecular Bone Mass and Uterumentioning
confidence: 99%
“…A portion of the AF-2 domain resides in H12, and it was proposed that the dislocation of H12 causes ICI-dependent LBD homodimerization involving the F-domain of ERα, which facilitates dimerization. Involvement of the F-domain in the antagonist-dependent LBD dimerization occurred not only with the AF-2-mutated ERα but also with WT ERα (28). A portion of the antagonistic effect of ICI on WT ERα results from the stimulation of ERα proteolysis (28)(29)(30), and it was recently reported that ICI induces SUMOylation of human ERα protein and that the mutations of H12 reduced SUMOylation in the presence of ICI (31).…”
Section: Ici Acts As An Erα Agonist On Trabecular Bone Mass and Uterumentioning
confidence: 99%
See 2 more Smart Citations
“…In the AF2ERKI mice, estradiol (E2) does not induce any estrogen responsive functions even though AF-2-mutated ER␣ protein is expressed in the tissues and resulted in an identical phenotype to ER␣ null mutant mice (␣ERKO), supporting a major role of AF-2 in E2-mediated responses in some tissues. One of the interesting characteristics of the AF2ER mutant receptor is an antagonist reversal activity, where antagonists such as 4-hydroxytamoxifen (4OHT) and fulvestrant/ ICI182780 (ICI) activate the AF2ER mutant receptor through the activation of AF-1 in a similar manner to SERM-mediated ER␣ activation (14,16). The antagonist reversal through AF-1 was tissue-selective as it was observed in certain tissues of AF2ERKI mice but not all tissues (14,15), suggesting that the AF-1 activity is different in the various tissues.…”
mentioning
confidence: 99%